Extra cup of tea intake associated with increased risk of Alzheimer’s disease: Genetic insights from Mendelian randomization - Sun, Yuxuan; Liang, Zixin; Xia, Xiaoxuan; Wang, Maggie Haitian; Zhu, Chengming; Pan, Yihang; Sun, Rui (Frontiers in Nutrition, 2023)
Background: Observational studies report inconclusive effects of tea consumption on the risk of Alzheimer’s disease (AD), and the mechanisms are unclear. This study aims to investigate the effects of genetically predicted tea intake (cups of tea consumed per day) on AD, brain volume, and cerebral small vessel disease (CSVD) using the two-sample Mendelian randomization (MR) method. Methods: Summary statistics of tea intake were obtained from UK Biobank (N = 447,485), and AD was from the International Genomics of Alzheimer’s Project (N = 54,162). Genetic instruments were retrieved from UK Biobank using brain imaging-derived phenotypes for brain volume outcomes (N > 33,224) and genome-wide association studies for CSVD (N: 17,663 - 48,454). Results: In the primary MR analysis, tea intake significantly increased the risk of AD using two different methods (ORIVW = 1.48, 95% CI: [1.14, 1.93]; ORWM = 2.00, 95% CI: [1.26, 3.18] and reached a weak significant level using MR-Egger regression (p < 0.1). The result passed all the sensitivity analyses, including heterogeneity, pleiotropy, and outlier tests. In the secondary MR analysis, per extra cup of tea significantly decreased gray matter (βWM = -1.63, 95% CI: [-2.41, -0.85]) and right hippocampus volume (βWM = -1.78, 95% CI: [-2.76, -0.79]). We found a nonlinear association between tea intake and AD in association analysis, which suggested that over-drinking with more than 11 cups per day might be a risk factor for AD. Association analysis results were consistent with MR results. Conclusion: This study revealed a potential causal association between per extra cup of tea and an increased risk of AD. Genetically predicted tea intake was associated with a decreased brain volume of gray matter and the right hippocampus, which indicates that over-drinking tea might lead to a decline in language and memory functions. Our results shed light on a novel possible mechanism of tea intake to increase the risk of AD by reducing brain volume.